GSK-3 as potential target for therapeutic intervention in cancer - McCubrey, James A.; Steelman, Linda S.; Bertrand, Fred E.; Davis, Nicole Marie; Sokolosky, Melissa; Abrams, Stephen L.; Montalto, Giuseppe; D'Assoro, Antonino B.; Libra, Massimo; Nicoletti, Ferdinando; Maestro, Roberta; Basecke, Jorg; et al. (My University, 2014)
The serine/threonine kinase glycogen synthase kinase-3 (GSK-3) was initially identified and studied in the regulation of glycogen synthesis. GSK-3 functions in a wide range of cellular processes. Aberrant activity of GSK-3 has been implicated in many human pathologies including: bipolar depression, Alzheimer's disease, Parkinson's disease, cancer, non-insulin-dependent diabetes mellitus (NIDDM) and others. In some cases, suppression of GSK-3 activity by phosphorylation by Akt and other kinases has been associated with cancer progression. In these cases, GSK-3 has tumor suppressor functions. In other cases, GSK-3 has been associated with tumor progression by stabilizing components of the beta-catenin complex. In these situations, GSK-3 has oncogenic properties. While many inhibitors to GSK-3 have been developed, their use remains controversial because of the ambiguous role of GSK-3 in cancer development. In this review, we will focus on the diverse roles that GSK-3 plays in various human cancers, in particular in solid tumors. Recently, GSK-3 has also been implicated in the generation of cancer stem cells in various cell types. We will also discuss how this pivotal kinase interacts with multiple signaling pathways such as: PI3K/PTEN/Akt/mTORC1, Ras/Raf/MEK/ERK, Wnt/beta-catenin, Hedgehog, Notch and others.
Keywords: GSK-3; cancer stem cells; Wnt/beta-catenin; PI3K; Akt; mTOR; Hedgehog; Notch; Targeted Therapy; Therapy Resistance; Mutations; Rapamycin